Sitting time and associated factors among Portuguese older adults: results from Nutrition UP 65 - Sousa, Ana Sofia (2022)
Older adults are particularly susceptible to sedentary behaviours. Sitting time has been increasingly referred to as a potentially modifiable risk factor in the prevention of chronic diseases. Identifying factors associated with sitting time, particularly those that are modifiable, will allow for more effective public health strategies. This study aimed to describe sitting time among Portuguese older adults and to evaluate associated factors. A cross-sectional study including 1423 older adults ≥ 65 years old was conducted. Sitting time was assessed with the International Physical Activity Questionnaire. Socio-demographic, health, anthropometric and functional variables were collected. Bivariate and multivariate linear regression models were conducted to study the association between these variables and sitting time. The median of sitting time was 300 min/day (interquartile range = 240 min/day), which is equal to 5 h/day. The following factors were directly associated with longer sitting time: being male, age ≥ 80 years, living in Central or Southern Portugal, being retired from work, as well as presenting low physical activity, obesity or longer time to walk 4.6 metres. On the other hand, being married, having higher education and higher household income were inversely associated with longer sitting time. It can be concluded that Portuguese older adults spend a considerable amount of time sitting per day. Potentially modifiable risk factors associated with longer sitting time in this population were related to nutritional status and functional ability.